Is Consumer Trust Able to Intervening in Purchasing Decisions VJO Café and Bistro - Sa’adah, Nailis; Lusianti, Dina; Wismar'ein, Dian (Universitas Muria Kudus, 2024)
This research aims to determine the influence of online customer reviews and brand image on purchasing decisions with consumer trust as an intervening variable at VJO Café and Bistro. The population in this study were customers of VJO Café and Bistro Kudus. The sample consisted of 120 respondents. Data analysis uses Structural Equation Modeling. The research results show that online customer reviews have a positive and significant effect on consumer trust, brand image has a positive and significant effect on consumer trust, online customer reviews have a positive and significant effect on purchasing decisions, brand image has a positive and insignificant effect on purchasing decisions, consumer trust has an effect positive and significant on purchasing decisions. Consumer trust can be a mediating variable in the relationship between online customer reviews and purchasing decisions, and consumer trust can be a mediating variable in the relationship between brand image and purchasing decisions.